Effectiveness of 2% peracetic acid for the disinfection of gutta-percha cones - Salvia, Ana Carolina Rodrigues Danzi [UNESP]; Teodoro, Guilherme Rodrigues [UNESP]; Balducci, Ivan [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; de Oliveira, Simone Helena Gonçalves [UNESP] (FapUNIFESP (SciELO), 2011)
The aim of this study was to evaluate the effectiveness of 2% peracetic acid for the disinfection of gutta-percha cones contaminated in vitro with Escherichia coli, Staphylococcus aureus, Streptococcus mutans, Candida albicans and Bacillus subtilus (in spore form). Two hundred and twenty-five gutta-percha cones were contaminated with standardized suspensions of each microorganism and incubated at 37°C for 24 h. The cones were divided into 10 experimental groups (n = 15), according to the microorganism tested and disinfection testing times. The disinfection procedure consisted of immersing each cone in a plastic tube containing the substance. The specimens remained in contact with the substance for 1 or 2.5 minutes. Afterwards, each cone was transferred to a 10% sodium thiosulphate solution (Na2S2O3) to neutralize the disinfectant. Microbial biofilms adhering to the cones were dispersed by agitation. Aliquots of 0.1 ml of the suspensions obtained were plated on Sabouraud dextrose agar, or brain and heart infusion agar, and incubated at 37°C for 24 h. The results were expressed in colony forming units (CFU/ml) and the data were submitted to the Wilcoxon Signed Rank Test (level of significance at 0.05). A significant reduction was observed, after 1 minute of exposure, in the test solution for C. albicans (p = 0.0190), S. aureus (p = 0.0001), S. mutans (p = 0.0001), B. subtilis (p = 0.0001), and E. coli (p = 0.0001). After 2.5 minutes of exposure, 100% of the microbial inocula were eliminated. It was concluded that the 2% peracetic acid solution was effective against the biofilms of the tested microorganisms on gutta-percha cones at 1 minute of exposure.
Keywords: Disinfection; Endodontics; Microbiology